2016
DOI: 10.1021/acsami.5b11353
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids as Electrolytes for Electrochemical Double-Layer Capacitors: Structures that Optimize Specific Energy

Abstract: Key parameters that influence the specific energy of electrochemical double-layer capacitors (EDLCs) are the double-layer capacitance and the operating potential of the cell. The operating potential of the cell is generally limited by the electrochemical window of the electrolyte solution, that is, the range of applied voltages within which the electrolyte or solvent is not reduced or oxidized. Ionic liquids are of interest as electrolytes for EDLCs because they offer relatively wide potential windows. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
152
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 71 publications
3
152
1
Order By: Relevance
“…[TFSI] were clearly highert han those measured in [EMI]BF 4 and [EMI] [OTf]. [20] In line with this trend, Ta shimae tal. reported that their AC electrodes, regardless of the conducting agent (acetylene black or Ketjenblack)u sed, showed highers pecific capacitances in [EMI][TFSI] compared to those in [EMI]BF 4 IL in the range of 0-50 8C.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…[TFSI] were clearly highert han those measured in [EMI]BF 4 and [EMI] [OTf]. [20] In line with this trend, Ta shimae tal. reported that their AC electrodes, regardless of the conducting agent (acetylene black or Ketjenblack)u sed, showed highers pecific capacitances in [EMI][TFSI] compared to those in [EMI]BF 4 IL in the range of 0-50 8C.…”
Section: Introductionsupporting
confidence: 67%
“…As for the IL anion effects, with the [EMI][TFSI],[EMI]BF 4 ,and [EMI][FSI] as electrolyte the capacitances were 93, 108, and1 20 Fg À1 ,r espectively,a t0 .5 Ag À1 .A t 10 Ag À1 ,t he capacitances decreased to 10, 17, and 60 Fg À1 , correspondingt o1 1%,1 6%,a nd 50 %r etention, respectively, compared to those measured at 0.5 Ag À1 .T he capacitance reductionw ith increasing appliedc urrent density can be attributed to the kinetic limitation of ion adsorption/desorptiona nd migration in the AC pores. [15,17,31,32] TFSI À can withstand a higher anodic potential, [20] resulting in al arger V cell .H owever, its large size (see Table S2) occupies more space on the AC surface and thus decreases the charged ensity that can be stored. Moreover FSI À decomposed at al ower potential than BF 4 À and TFSI À .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these different features of ILs based on different cations have a significant influence on the P s as well as the ED of SCs . It was also observed that ammonia‐based ILs display a larger ESW as compared to pyridinium‐ and imidazolium‐based ILs, the two latter offering higher cell capacitance, however . Nevertheless, pyrrolidinium, imidazolium, as well as pyridinium cations have been plagued with toxicity issues affecting the greenness of such ILs as against organic electrolytes used for the same purpose.…”
Section: Ils and The Influence Of Their Viscosity On The Performancementioning
confidence: 99%
“…[11][12][13][14] Ionic liquids (ILs) are a class of material that has been extensively studied and are considered as an alternative to organic solvent-based electrolytes in energy storage devices, not only due to their intrinsic ionic conductivity but also due to their high chemical and thermal stability, non-flammability, negligible vapour pressure, high electrochemical stability and they can be considered to be less hazardous than organic solvent-based electrolytes. [15][16][17][18] ILs are salts that normally contain an asymmetric cation and an anion with delocalised charge, which results in weak ionic interactions. Conventionally, salts that display a melting temperature lower than 100 1C are considered to be ILs.…”
Section: Introductionmentioning
confidence: 99%